2017
DOI: 10.1111/scs.12488
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in patients with lymphoedema – a cross‐sectional study

Abstract: This study indicates that about 20% of the patients with lymphoedema had major impact on their HRQoL. More effort and research is needed to identify, understand and support groups of patients with severe lymphoedema-related problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
0
10
1
Order By: Relevance
“…Primary lymphedema occurs rarely (in approximately 1 in 100,000 people), and is the consequence of inherited genetic predisposition and abnormality in the construction of the lymphatic system. 1 , 2 Secondary lymphedema occurs more frequently. In the developing countries, its etiology is associated with parasitic infections which affect as many as 300 million people globally, 3 making them the most common cause of lymphedema worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary lymphedema occurs rarely (in approximately 1 in 100,000 people), and is the consequence of inherited genetic predisposition and abnormality in the construction of the lymphatic system. 1 , 2 Secondary lymphedema occurs more frequently. In the developing countries, its etiology is associated with parasitic infections which affect as many as 300 million people globally, 3 making them the most common cause of lymphedema worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…According to various studies, lymphedema following cancer treatment appears in up to 50% of the affected cases. 1 , 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…The study by Klernäs et al [ 42 ] reported that lymphedema had an effect on the QoL in 20% of patients. QoL assessment tended to decrease with age, with a significant correlation in the psychosocial area (rs=0.194, P =0.028).…”
Section: Discussionmentioning
confidence: 99%
“…QoL assessment tended to decrease with age, with a significant correlation in the psychosocial area (rs=0.194, P =0.028). Compared to the general Swedish population, patients with lymphedema evaluated their overall health, vitality,and social functioning by SF36 as significantly lower [ 42 ]. In our study, we assumed that lymphedema reduction and age would be predictors of improved QoL assessment in patients.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence is 30-50% both in the upper limb after breast cancer treatment and in the lower limb after gynecological, however a bit lower, about 10%, in prostate cancer [2][3][4]. Recent studies have reported that lymphedema secondary to cancer treatment has a negative impact on quality of life and more on patients with lower limb than with upper limb lymphedema [5].…”
Section: Introductionmentioning
confidence: 99%